Exploring the Role of CACNA1C, ZNF804A and SLC6A4 in Schizophrenia through Epigenomics and Bioinformatics - Ch, Bhargavi; V, Lakshmi (Journal of Neonatal Surgery, 2025)
Schizophrenia (SCZ) is a complex neuropsychiatric condition in which genetic vulnerability interacts with environmental exposures to influence disease risk and clinical outcomes. Emerging non-genetic causes include early-life stress, substance use and urban living environments, which have been found to interact with inherent genetic predisposition. Recent advances in epigenomics and bioinformatics have illuminated the mechanisms through which these environmental insults may alter gene expression, particularly via DNA methylation, chromatin remodeling and transcription factor binding. Genes such as CACNA1C, ZNF804A and SLC6A4 exemplify loci where regulatory changes may mediate gene-environment interactions. Bioinformatics tools like GTEx, ENCODE, 3DSNP, and methylation datasets from epigenome-wide association studies (EWAS) now provide special perspectives into these molecular processes. This review highlights key epigenetic mechanisms linking environmental exposures to SCZ pathogenesis and explores how integrative computational analyses are enhancing our understanding of this complex disorder. A deeper appreciation of gene- environment interactions may ultimately inform personalized interventions and risk stratification in SCZ care.